Influence of environmental parameters on corrosion mechanisms of steels used in oil field. Issue 11 (13th March 2015) - Sow, L.; Idrac, J.; Mora, P.; Font, E.
<x xml:space="preserve">Abstract</x> The influence of several environmental parameters on NACE SSC A tests results was analysed in this study. The effect of dissolved oxygen, pH and partial pressure of hydrogen sulfide (H2S) on corrosion and cracking susceptibility has been experimented. These experiments were done on steel wires used in oil industry. Experiments have proved that the pH value is the most influential parameter on both corrosion and cracking susceptibility of samples. H2S partial pressure also has a negative effect on cracking susceptibility. The dissolved oxygen content appeared as an incriminating factor on corrosion but can reduce the cracking susceptibility of samples.